Bioavailability Study of Propranolol Patch - Arsul, Muh Ikhlas; Rahman, Latifah; Lidjajah, Agnes (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2020)
Bioavailability is a measure of the rate and amount of drug or active ingredient that is absorbed by a drug product and available at the site of action. By definition, the bioavailability of a drug when administered intravenously is 100%. However, when a drug is given by a different route of administration, its overall bioavailability will decrease (since the drug is not completely absorbed and metabolized first pass effect) or may vary from patient to patient. Bioavailability is very important in pharmacokinetics. One of them is that bioavailability needs to be taken when calculating the doses for administering a drug other than by intravenous route. The aim of this study was to describe the bioavailability of propranolol in patch preparations. Propranolol is made in patch formulations using menthol, PEG, and various combinations of PVP and Eudragit. PVP and Eudragit each dissolved in alcohol and then mixed until homogeneous. Propranolol was dissolved with a menthol solution and then mixed into a solution of PVP and Eudragit. Finally, PEG is added to the solution and stirred until homogeneous and then poured into the patch mold. The patches produced were then measured for each patch and bioavailability assay. The patch formula produced can be used transdermally, but of the three formulas, the F3 formula with a ratio of PVP K30 and Eudragit RS-100 3: 7 gives the best results with a tmax of 2 hours, Cmax 79.33 µg / ml and AUC 49.07 µg hours / ml.